Pemanfaatan tanaman sorgum sebagai pakan ternak ruminansia di lahan kering - Harmini Harmini (Livestock and Animal Research, 2021)
Objective: The objective of this study is to review the use of sorghum as a feed source for ruminants that it can developed on dry land.Results: Sorghum is a cereals that can grow on dry land. Sorghum is source of food, biofuel and animal feed. Sorghum plants have high nutritional value and can replace other feed sources, because they have a high chemical composition, vitamins, minerals, and energy content. Sorghum contains crude protein, fat and ash 9.9; 2.7 and 11.45% respectively. In fresh conditions, sorghum leaves and stems cannot last long, therefore it can be stored in silage to extend their shelf life so that they can be used in the dry season.Feeding leaves, straw, byproducts with sorghum have been positively influenced such as increased antilmytic effect in sheep, feed consumption, digestibility in livestock, rumen fermentation, VFA, pH-rumen, digestibility and feed efficiency of the feed of the animal also meat and milk production of goats.Conclusions: Sorghum is potentially produced as a feed source for ruminants due to good nutritional content and can be developed in dry land.